Embracing Students’ Self Confidence: Bringing Instagram Into English Speaking Classroom, Why Not? - Kharisma Mutiara; Sri Marmanto; Slamet Supriyadi (Journal Prakarsa Paedagogia, 2021)
As one of the four English skills that has to be mastered, English learners still see that speaking mastery is challenging. Many of them are difficult to speak, although their writing, reading, and listening skills are good. This research presents a classroom action research of using Instagram in English speaking classroom with students in a private senior high school in Surakarta. The purpose of this research is to propose the use of Instagram as a social media to teach speaking as well as to find out the students' attitude towards the use of Instagram in enhancing their speaking skills. The study revealed that Instagram used in English speaking classroom brings effective meaning for them in learning English. Instagram also brings a positive attitude to students so that they can learn to speak English more easily.